The Post-EDSA constitutional commissions (1986-1992) self assessments and external views - Abueva, Jose Veloso 1928-.; Roman, Emerlinda Ramos (Quezon City University of the Philippines Press, 1998)
"This book rounds out the assessments of the various political and governmental institutions that were restored and rebuilt under the 1987 Constitution, following the EDSA Revolution in February 22-25, 1986 that ended the dictatorship of Ferdinand E. Marcos (1972-1986).
Part I. Towards honesty, efficiency, and professionalism in the bureaucracy -- Chapter 1. The Civil Service Commission : a self-assessment / Patricia S. Sto. Tomas -- Chapter 2. The CSC : contemporary views and assessments / Jaime B. Veneracion, Amelia P. Varela -- Part II. Towards peaceful, honest, orderly, and credible elections -- Chapter 3. The Commission on Elections : a self-assessment / Christian S. Monsod -- Chapter 4. The COMELEC : contemporary views and assessments / Raul P. De Guzman, Pacifico A. Agabin -- Part III. Reducing dishonesty, waste, and irresponsibility in the government -- Chapter 5. The Commission on Audit : a self-assessment / Eufemio C. Domingo -- Chapter 6. The COA : contemporary views and assessments / Ledevina V. Cariño, Teresa F. Bernabe -- Part IV. Protecting human rights -- Chapter 7. The Commission on Human Rights : a self-assessment / Mary Concepcion Bautista -- Comment on the Amnesty International Report / Commission on Human Rights -- Chapter 8. The CHR : contemporary view and assessment / Pacifico A. Agabin -- Part V. Recovering stolen wealth -- Chapter 9. The Presidential Commission on Good Government : a self-assessment / David A. Castro -- Chapter 10. The PCGG : contemporary views and assessments / Jovito R. Salonga , Raul J. Palabrica, Belinda Olivarez-Cunanan, Vicente Albano Pacis, Manila Bulletin, Salvador T. Reyes -- Appendices.
Keywords: Administrative agencies -- Evaluation. -- Philippines; Philippines -- Politics and goverment -- 1986-1992.